THE GENETIC ALGORITHM APPLICATION FOR MEASURING THE REVERSE CHANNEL OPTIMATION PERFORMANCE WIRELESS DSCDMA NETWORK SYSTEM - Haris Fadhilah; Yusak Yudianto; Yoedy Moegiharto; Wahjoe Tjatur (SAINTEKBU, 2008)
The third generation wireless DS-CDMA networks are expected to support a wide varietyof multimedia services such as high quality voice and data continuous (facsimile). The systemquality of DS-CDMA is shown as bit error probability values or bit error rate (BER) both voicechannel and continuous data channel. Bit error probability values are influenced by interferenceof the other users voice and data continuous (facsimile) .In the Final Project is made the genetic algorithm software for measuring the optimalsystem quality, specially for reverse channel. The optimal value result to explain the numberactive voice and data users that results minimum probability value on voice channel or datacontinuous (facsimile).